2018
DOI: 10.1038/s41467-018-06701-4
|View full text |Cite|
|
Sign up to set email alerts
|

Host-associated niche metabolism controls enteric infection through fine-tuning the regulation of type 3 secretion

Abstract: Niche-adaptation of a bacterial pathogen hinges on the ability to recognize the complexity of signals from the environment and integrate that information with the regulation of genes critical for infection. Here we report the transcriptome of the attaching and effacing pathogen Citrobacter rodentium during infection of its natural murine host. Pathogen gene expression in vivo was heavily biased towards the virulence factor repertoire and was found to be co-ordinated uniquely in response to the host. Concordant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 80 publications
0
40
0
Order By: Relevance
“…In an analogous manner, cobalamin is required for enzymatic activity of propanediol dehydratase, which breaks down 1,2-propanediol, a metabolite that enhances Salmonella growth [20]. Additionally, cobalamin-dependent degradation of 1,2-propanediol releases breakdown product propionate, which promotes Citrobacter rodentium virulence during infection of the mammalian gastrointestinal tract [21] ( C . rodentium is a murine pathogen frequently used to model EHEC and enteropathogenic E .…”
Section: Introductionmentioning
confidence: 99%
“…In an analogous manner, cobalamin is required for enzymatic activity of propanediol dehydratase, which breaks down 1,2-propanediol, a metabolite that enhances Salmonella growth [20]. Additionally, cobalamin-dependent degradation of 1,2-propanediol releases breakdown product propionate, which promotes Citrobacter rodentium virulence during infection of the mammalian gastrointestinal tract [21] ( C . rodentium is a murine pathogen frequently used to model EHEC and enteropathogenic E .…”
Section: Introductionmentioning
confidence: 99%
“…216 Similarly, microbiome-derived 1,2-propanediol strengthens virulence factor expression in pathogens, supporting the intestinal colonization and expansion of pathogens such as C. rodentium. 217 Additional metabolite-mediated modulation of host metabolism Imidazole propionate, produced by type 2 diabetes-associated bacteria as a metabolite of histidine, is heightened in type 2 diabetes and impairs glucose tolerance and insulin signaling, a process achieved by inhibiting insulin receptor substrate (IRS) in a p38g/p62/mTORC1-dependent manner. 218 In a similar vein, the gut microbiome that harbors tyrosine phenol-lyase can catabolize dietary tyrosine into the precursor phenyl sulfate.…”
Section: Additional Microbially Derived Metabolitesmentioning
confidence: 99%
“…Key to revealing novel and physiological phenotypes is the selection of an appropriate mouse strain, or knock-out mice (Simmons et al, 2002 ; Zheng et al, 2008 ; Carson et al, 2019 ). To highlight some examples, the mouse model has delineated Tir, NleA and NleB as essential effectors for efficient colonization (Deng et al, 2003 ; Mundy et al, 2004 ; Kelly et al, 2006 ), demonstrated the impact of individual effectors deletions on host physiology, such as EspO and EspS impacting CCH (Berger et al, 2018 ; Connolly et al, 2018 ), and substantiated in vitro data indicating Map impacts colonic oxygen availability through mitochondrial disruption (Berger et al, 2017 ). Recently, mouse-specific differences in infection signatures have been identified through RNAseq and proteomics (Kang et al, 2018 ; Carson et al, 2019 ); it remains to be seen whether these differences are fine-tuned by the synergistic action of the effectors.…”
Section: Defining Roles For the Effectors During Infectionmentioning
confidence: 99%